Using contrast-enhanced ultrasound to guide a successful biopsy of a splenic sarcomatoid carcinoma. (February 2020) - Leenknegt, Benjamin; Moore, Stephen; Fang, Cheng; Kibriya, Nabil; Gregory, Stephen; Cancuri, Osman; Sidhu, Paul S; Yusuf, Gibran
Introduction: Splenic lesions are uncommon and frequently cause a diagnostic dilemma, often with non-specific findings on both ultrasound and cross-sectional imaging with histological confirmation necessary. To reduce patient morbidity, primarily from haemorrhage and to increase diagnostic yield, precise imaging and biopsy targeting are needed. Case: We present a case of an indeterminate complex splenic lesion, with areas of necrosis which required histological diagnosis. Contrast-enhanced ultrasound-guided percutaneous core needle biopsy was undertaken to provide real-time imaging guidance, increasing viable lesion targeting and helping to avoid areas of necrosis. Conclusion: Contrast-enhanced ultrasound guidance of the percutaneous core needle biopsy allowed increased operator confidence in lesional targeting accuracy and reduced the number of passes required for biopsy, simultaneously maximising histological yield and minimising patient morbidity.